ALBERT THE GREAT ON NATURE AND THE PRODUCTION OF HERMAPHRODITES: THEORETICAL AND PRACTICAL CONSIDERATIONS. (2019) - RESNICK, IRVEN M.
Abstract : Despite its rarity, hermaphroditism is often discussed in medieval texts in theoretical and practical contexts by canonists, theologians, and natural philosophers. For the canonist or theologian, hermaphroditism raised questions concerning baptism, marriage, entry to clerical orders, and legal status. For the natural philosopher, the hermaphrodite seemed to violate the strict dichotomy of male and female. Here I examine Albert the Great's natural-philosophical treatment of hermaphroditism. Albert rejects the view that hermaphrodites constitute a "third sex" and instead invokes Aristotle's authority to show that hermaphrodites are a "monstrous" flaw in nature. He carefully investigates the manner in which nature produces hermaphrodites in the womb and introduces a discussion of the generative capacity of hermaphrodites themselves. He concludes that they are incapable of reproducing in and of themselves (i.e., they are incapable of auto-fecundation) although they seem able to generate in another individual through coition.